2018
DOI: 10.2991/itmr.7.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Mental and Physical Fatigue

Abstract: Although Internet addiction and fatigue are issues of concern among university students, the association between these phenomena has not been examined. In a unique contribution to the literature, this study examined if Internet addiction differentially influenced mental and physical fatigue in a sample of Moroccan students. Results indicate students with Internet addiction have significantly higher levels of mental and physical fatigue than students without Internet addiction. The findings extend understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
(87 reference statements)
0
11
0
2
Order By: Relevance
“…This may be particularly the case for college students who are often not adept at handling sudden and large life stressors ( 40 , 41 ), putting them at greater risk for developing depressive symptoms. As fatigue is a common byproduct of depleted psychological resources, risk factors [e.g., rumination; ( 42 , 43 )] and protective factors [e.g., resiliency; ( 44 )] for said resources may, respectively, exacerbate and mitigate the onset of physical and psychological fatigue among individuals. Specifically, Luceño-Moreno et al ( 34 ) found a strong negative relation between resilience and experience of emotional exhaustion among those impacted by COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…This may be particularly the case for college students who are often not adept at handling sudden and large life stressors ( 40 , 41 ), putting them at greater risk for developing depressive symptoms. As fatigue is a common byproduct of depleted psychological resources, risk factors [e.g., rumination; ( 42 , 43 )] and protective factors [e.g., resiliency; ( 44 )] for said resources may, respectively, exacerbate and mitigate the onset of physical and psychological fatigue among individuals. Specifically, Luceño-Moreno et al ( 34 ) found a strong negative relation between resilience and experience of emotional exhaustion among those impacted by COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, a few studies have assessed that IA and musculoskeletal discomfort. One cross-sectional study showed that college students with IA have significantly higher levels of physical fatigue than college students without IA (Bachleda and Darhiri, 2018). Another study reported that IA was positively associated with musculoskeletal pain in adolescents (Tülay and Ejder, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in motivation and willingness to exert physical effort are noted across psychiatric conditions including Major Depressive Disorder, addiction, and chronic fatigue (Cohen et al, 2001;Sharpe and Wilks, 2002;Demyttenaere et al, 2005;Bachleda and Darhiri, 2018). For example, patients with Major Depressive Disorder report trying harder even though they objectively exert less effort (Cléry-Melin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%